Reality show [compact disc] - Sullivan, Jazmine, 1987- (RCA Records, 2015)
Four years after the release of "Love me back", Grammy nominated singer-songwriter Jazmine Sullivan is back with her third studio album. The CD's first single, "Dumb" includes an appearance from hip-hop star Meek Mill.